P204 Digital interventions to improve adherence to maintenance medication in asthma: a Cochrane systematic review. (11th November 2022) - Chan, A; De Simoni, A; Wileman, V; Holliday, L; Newby, CJ; Chisari, C; Ali, S; Zhu, N; Padakanti, P; Pinprachanan, V; Ting, V; Griffiths, CJ
Abstract : Background: Asthma affects 339 million patients globally. Poor medication adherence leads to increased symptoms, exacerbations, hospitalisations, and healthcare utilisation. The impact of digital adherence interventions on adherence and asthma outcomes is unknown. Objectives: To determine the effectiveness of digital interventions for improving adherence to maintenance treatments in asthma. Methods: We included randomised controlled trials (RCTs) of any duration in any setting, comparing a digital adherence intervention with a non-digital adherence intervention/usual care in patients with asthma of all ages. Results: We included 40 parallel randomised controlled trials (RCTs) involving adults and children with asthma (n = 15, 207), 8 of which are ongoing. Pooled results showed that digital interventions may increase adherence (mean difference of 14.66 percentage points, 95% confidence interval (CI) 7.74 to 21.57; likely to be clinically significant in those with poor baseline adherence. Subgroup analysis by type of intervention was significant (P = 0.001), with better adherence with electronic monitoring devices (EMDs) and short message services (SMS). Digital interventions were likely to improve asthma control (standardised mean difference (SMD) 0.31 higher, 95% CI 0.17 to 0.44). They may reduce asthma exacerbations (risk ratio 0.53, 95% CI 0.32 to 0.91). Digital interventions may result in a slight change in unscheduled healthcare utilisation. School or work absence data could not be included for meta-analysis due to the heterogeneity and the low number of studies. They may result in little or no difference in lung function (forced expiratory volume in one second (FEV1 )): there was an improvement of 3.58% predicted FEV1, 95% CI 1.00% to 6.17%). Digital interventions likely produce a small increase in quality of life (SMD 0.26 higher, 95% CI 0.07 to 0.45). Acceptability data showed positive attitudes towards digital interventions. There were no data on cost-effectiveness or adverse events. Conclusions: Overall, digital interventions may result in a large increase in adherence. There is moderate-certainty evidence that digital adherence interventions likely improve asthma control to a degree that is clinically significant, and likely slightly increase quality of life with potential reduction in asthma attacks. Future studies should use consistent adherence and outcome measures to enable comparisons. Please refer to page A215 for declarations of interest related to this abstract.